2004
DOI: 10.1038/sj.bjc.6601578
|View full text |Cite
|
Sign up to set email alerts
|

Major depression in outpatients attending a regional cancer centre: screening and unmet treatment needs

Abstract: A screening programme designed to identify cases of Major Depressive Disorder (MDD) in patients attending a Regional Cancer Centre outpatient department was established. It comprised two stages: (1) The Hospital Anxiety and Depression Scale (HADS) selfrating questionnaire administered by a touch-screen computer; (2) we interviewed patients with high scores on the HADS (15 or more total score) over the telephone using the depression section of the Structured Clinical Interview for DSMIV (SCID). A large consecut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
159
3
9

Year Published

2004
2004
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 210 publications
(182 citation statements)
references
References 29 publications
11
159
3
9
Order By: Relevance
“…The point prevalence of depression among this group of breast cancer survivors is much lower than reported in some previous studies [20], but at 9%, it is in line with rates in primary care settings of 5-10% [21] and rates reported in some studies of cancer outpatients [3,22]. There is some evidence that after an initial rise, the prevalence of depression decreases over time following the diagnosis of breast cancer [1].…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The point prevalence of depression among this group of breast cancer survivors is much lower than reported in some previous studies [20], but at 9%, it is in line with rates in primary care settings of 5-10% [21] and rates reported in some studies of cancer outpatients [3,22]. There is some evidence that after an initial rise, the prevalence of depression decreases over time following the diagnosis of breast cancer [1].…”
Section: Discussionsupporting
confidence: 81%
“…The EDS has not yet been validated as a screen for psychological distress and there are limited studies on HADS-T. Where studies on the use of HADS-T to screen for anxiety and depression exist, there is no consistent definition for 'psychological distress', with some studies incorporating all psychiatric disorders and others taking a narrower view. In practice [3], tests which screen for a variety of psychiatric problems are likely to be more useful in follow-up patient care. On this basis, the use of the HADS-T and the EDS to screen for psychological distress can be recommended above their use to screen for depression alone, although the appropriate cut-off scores would need to be validated with a consistent definition of psychological distress in a larger population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, a study by Sharpe et al [245] found only 49% of patients identified as having major depressive disorder reported speaking to their doctors about depression, and only 15% of all patients identified as having major depressive disorder received a potentially effective evidence-based treatment such as a therapeutic dose of antidepressants or formal psychological treatment.…”
Section: Antidepressant Usementioning
confidence: 99%
“…Hospital Anxiety and Depression Scale (HADS) (Zigmond and Snaith, 1983): Anxiety and depressive symptoms were assessed with this 14-item self-rated scale designed for use in the medically ill (see companion paper Sharpe et al, 2003). (Harrison et al, 1994): Patient's concerns were rated using this 14-item checklist, each concern being rated on a five-point scale from 'not a worry' to 'extremely worried'.…”
Section: Structured Clinical Interview For Dsm-iv (Scid)mentioning
confidence: 99%